Gestão de operações em serviços de check-in em aeroportos: um estudo de caso sobre o impacto do uso de componentes de TI no aeroporto internacional de São Paulo-Guarulhos - Reis, Filipe Coutinho Pereira dos (2010)
The objective of this study is to analyze how the adoption of three technological components could increase the integration, efficiency and quality of the check-in process at Guarulhos international airport, serving the city of São Paulo. After an introduction on the relevance of the subject, and based on the cases of Las Vegas McCarran and London Heathrow – Terminal 5, the characteristics of the identified elements are explained through a review of the theoretical referential. The methodological technique chosen was the case study, which led to the definition of four research categories: modularity, mass customization, the redesign of the business network through the fourth level of integration through IT, and acceptance of self-services by passengers. As a next step, comparable global data for each research category and data for Guarulhos international airport was produced. The conclusion is composed by a proposed analysis for each research category and suggested items for further research.